Muscle Activity During Unilateral vs. Bilateral Battle Rope Exercises. Issue 10 (October 2015) - Calatayud, Joaquin; Martin, Fernando; Colado, Juan C.; Benítez, Josep C.; Jakobsen, Markus D.; Andersen, Lars L.
Abstract : Abstract: Calatayud, J, Martin, F, Colado, JC, Benítez, JC, Jakobsen, MD, and Andersen, LL. Muscle activity during unilateral vs. bilateral battle rope exercises. J Strength Cond Res 29(10): 2854–2859, 2015—High training intensity is important for efficient strength gains. Although battle rope training is metabolically demanding, no studies have quantified intensity of muscle activity during this type of training. This study analyzes muscle activity during unilateral alternating waves vs. bilateral waves of battle rope training. Twenty-one volunteers participated in a repeated-measures study on 2 different occasions. Surface electromyographic signals were recorded from the anterior deltoid (AD), external oblique (OBLIQ), lumbar erector spinae (LUMB), and gluteus medius (GM) during bilateral waves and unilateral waves and were normalized to the maximum voluntary isometric contraction (MVIC). Results showed that muscle activity ranged from 51%MVIC to 73%MVIC for AD, OBLIQ, and LUMB, whereas GM muscle activity was only 14–18%MVIC. OBLIQ activation was significantly greater (20%MVIC; p = 0.02) with the unilateral waves compared with the bilateral waves, whereas LUMB signal was significantly higher (16%MVIC; p = 0.001) with the bilateral waves compared with the unilateral waves. In conclusion, both wave movements can be used to provide moderate to high levels of muscle activity in the AD, OBLIQ, and LUMB. Fitness practitioners aiming for higher OBLIQ activity should perform unilateral waves, whereas the bilateral variation of the movement can be used for higher LUMB activity.